2021
DOI: 10.1002/ctm2.608
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin enhancer‐binding factor 2 promotes cell proliferation and DNA damage response in metastatic melanoma

Abstract: Background 1q21.3 amplification, which is frequently observed in metastatic melanoma, is associated with cancer progression. Interleukin enhancer‐binding factor 2 ( ILF2 ) is located in the 1q21.3 amplified region, but its functional role or contribution to tumour aggressiveness in cutaneous melanoma is unknown. Methods In silico analyses were performed using the TCGA SKCM dataset with clinical annotations and three melanoma microarray cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…ILF2, also known as nuclear factor 45 (NF45), is crucial for cell growth and the inflammatory response ( Du et al, 2019 ). Recent studies have shown that ILF2 can promote cell proliferation and the inflammatory response ( Jia et al, 2020 ; Zhang et al, 2021 ). ILF2 forms a complex with the 90 kDa interleukin enhancer binding factor 3 (NF90, ILF3) ( Zhao et al, 2005 ; Kuwano et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…ILF2, also known as nuclear factor 45 (NF45), is crucial for cell growth and the inflammatory response ( Du et al, 2019 ). Recent studies have shown that ILF2 can promote cell proliferation and the inflammatory response ( Jia et al, 2020 ; Zhang et al, 2021 ). ILF2 forms a complex with the 90 kDa interleukin enhancer binding factor 3 (NF90, ILF3) ( Zhao et al, 2005 ; Kuwano et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome 1q gains occurred in various human cancers, such as LUAD, LIHC, OV, BRCA, and multiple myeloma [ 32 , 34 , 35 ]. Chromosome 1q21.3 abnormalities are related to breast cancer recurrence, and they can promote cell proliferation and DNA damage response in metastatic melanoma [ 35 , 36 ]. SETDB1 is located in the 1q21.3 region that encodes a histone methyltransferase which regulates transcriptional repression, histone methylation, and gene silencing [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced cell viability and increased apoptosis rates observed in our experiments following SHMT2 knockdown were partially reversed by ILF2 overexpression. Additionally, upregulation of ILF2 was also testified to exacerbate cell invasion and metastasis in melanoma and to regulate EMT-related genes in pancreatic cancer PANC-1 cells [ 47 , 50 ]. In our experiments, ILF2 served as a promoter in the invasion, migration, and EMT process in SHMT2-knockdown CAL-27 cells.…”
Section: Discussionmentioning
confidence: 99%